Análisis de los indicadores financieros, una revisión de la evolución y aplicación de las razones - Apolo Vivanco, Evelyn Andrea (2015)
The aim of this paper is developing a financial management tool for the evolution of the reasons by DuPont method for defining when profitability is optimal linking the cost-benefit, the ability of the assets invested in equity to generate profit in order to measure the administrative efficiency and optimize resources. Starting from bibliographical sources of financial analysis, financial performance in order to have a clear view to reach the implementation of the proposal through the financial statements .The project was conceived as a model ,a business strategy for reliable information, identify potential risks to mitigate weaknesses and opportunities, make decisions with reliable bases